Teacher’s Problems and Strategies in Teaching Writing for the Seventh Grade Students at MTs Al-Hidayah - Raputri, Egi; Widi, Rahma (English Education Journal, 2023)
Generally, teaching writing is not an easy thing. This is because writing is more complex than other skills in English. This research aimed to find out the Indonesian English teachers’ problems and the strategies used in teaching and learning writing skills in the classroom. This research was conducted in MTs Al-Hidayah. The researchers occupied descriptive qualitative research as the research design. The data were collected by interviewing an English teacher and some students in the seventh grade, and by observing their classroom during teaching and learning writing skill activities. Besides, the researchers collected some documentation and video recordings to support the data and additional information. There were several results that the researchers found while conducting the research. The first result is about the problem faced by the English teacher which is related to the students’ ability. It consisted of the students' lack of vocabulary mastery, grammatical rules, low motivation, and lack of teachers’ class management. Then, the teaching strategy used by the teacher was the Grammatical Translation Method (GTM). Shortly, the problems faced by English teachers in teaching writing are mostly because of students’ lack of vocabulary and understanding of grammatical rules. To overcome those problems, the teacher applied the GTM. The function of this research is to give additional information to the teachers and readers about teachers’ problems and strategies of teaching writing.